Melacak Pemikiran Hukum Tariq Ramadan - Makmun, Moh. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
No one can deny that in the last 150 to 200 years, the history of mankind has undergone extraordinary changes that have had an impact on changing mindset and religious worldview. This article wants to know the thoughts of one of the contemporary figures named Tariq Ramadan. The rise of Islamic thought must involve reconciliation with the spiritual dimension on the one hand, and on the other hand renew commitment and rational and critical reading (ijtihad) from scriptural sources in the field of law and jurisprudence (fiqh). Must be able to distinguish which texts are eternal (the immutable, ath-thabit) and which can be changed (the changing, al-mutagayyir). Three things that must be considered in determining the concept of mashlahah, first, haqiqiyyah, are authentic and definitive, not speculative (wahmiyyah); second, kulliyyah, is general in nature, meaning that it does not only accommodate the interests of a person or group of people; third, it does not conflict with qath'i texts. Contemporary reading is done in mu'amalah's problem, while the issue of worship and aqeedah is not necessary, because it can be criticized, dangerous, and considered bid'ah.